2017
DOI: 10.1177/0885066617703348
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Hemogram Parameters and Survival of Critically Ill Patients

Abstract: We think that elevated MPV levels in an ICU patient should alert clinicians for worse outcome. Physicians should be more careful in the management of these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 20 publications
1
30
0
Order By: Relevance
“…Platelets play a role in important tasks in the human body, such as hemostasis and tissue regeneration. Depending on the increasing number of platelets and activity in the blood, thromboxane synthesis and synthesis of adhesion molecules increase, so that susceptibility to thrombosis occurs [9]. These causes have been the subject of research in the pathogenesis of cardiovascular diseases and their prognosis after treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Platelets play a role in important tasks in the human body, such as hemostasis and tissue regeneration. Depending on the increasing number of platelets and activity in the blood, thromboxane synthesis and synthesis of adhesion molecules increase, so that susceptibility to thrombosis occurs [9]. These causes have been the subject of research in the pathogenesis of cardiovascular diseases and their prognosis after treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In one study, Karagöz et al [35] categorized critically ill patients in two groups as deceased and discharged patients, and they examined the associations of hemogram parameters and especially MPV with mortality. They found strong association between increased MPV values and mortality [35]. Their results are not in agreement with our results.…”
Section: Discussionmentioning
confidence: 99%
“…Platelets are tend to have greater size when they are activated by inflammation or other stimuli (3). Association between MPV and inflammatory conditions have been demonstrated in various research in literature (4)(5)(6)(7)(8)(9)(10)(11)(12)(13). In a recent study it has been reported that, MPV of subjects with vitamin D deficiency, another condition that associated with low grade inflammation, have greater MPV values compared to subjects with normal serum vitamin D levels (14).…”
Section: Introductionmentioning
confidence: 98%